2020
DOI: 10.1101/2020.09.11.20192831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taste alteration in COVID-19: a rapid review with data synthesis reveals significant geographical differences

Abstract: To facilitate a timely understanding of the differences in the prevalence of gustatory disturbances (GD) in individuals infected with SARS-CoV-2, we undertook a rapid systematic review of articles published in the repository of the National Library of Medicine (MEDLINE/PubMed) and medRxiv from their inception until September 3, 2020. The minimum requirements for completing a restricted systematic review were met. Of the 431 articles retrieved, 61 eligible studies (28,374 confirmed COVID-19 cases) from 20 count… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In the systematic reviews analyzing smell and/or taste together, the range was 5.6-94%. The heterogeneity of these findings may be partially due to differences in the geographical distribution of this association 3 . Interestingly, when the prevalence was pooled on the total number of cases examined, olfactory and gustatory alterations were found in approximately half of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the systematic reviews analyzing smell and/or taste together, the range was 5.6-94%. The heterogeneity of these findings may be partially due to differences in the geographical distribution of this association 3 . Interestingly, when the prevalence was pooled on the total number of cases examined, olfactory and gustatory alterations were found in approximately half of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 93%
“…In agreement with the growing body of evidence, sudden onset of anosmia, ageusia or dysgeusia have now been recognized as major clinical characteristics of the disease and have been included in the list of key clinical criteria for case definition of COVID-19 by the European Centre for Disease Prevention and Control as well as other Public Health surveillance organizations across the world such as CDC, WHO 3 , and Public Health England 7 . However, it is not known whether concurrent olfactory and gustatory alterations may indeed represent the only clinical sign of SARS-CoV-2 infection in otherwise healthy patients.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Professor C. Hopkins, President of the British Rhinological Society, has noted that the loss of smell or taste may be the sole symptom of COVID-19 [ 91 ]. Several public health surveillance organizations, including the European Centre for Disease Prevention and Control, the Centers for Disease Control and Prevention, the WHO [ 92 ], and Public Health England, have incorporated the sudden onset of anosmia, ageusia, or dysgeusia into their primary clinical criteria for defining a COVID-19 case [ 93 ]. The present systematic review also found that general symptoms typically follow oral symptoms, particularly the loss of taste.…”
Section: Discussionmentioning
confidence: 99%
“…Novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an outbreak that emerged in China in December 2019, has rapidly evolved into a global pandemic and has become a persistent global health threat. Sudden onset of anosmia, ageusia, or dysgeusia has now been recognized as a major clinical characteristic of the disease and has been included in the list of key clinical criteria for case definition of COVID-19 by the European Centre for Disease Prevention and Control as well as other public health surveillance organizations across the world, such as the CDC, the WHO 1 and Public Health England 2 .…”
Section: Introductionmentioning
confidence: 99%